Supramolecular chemistry assisted construction of ultra-stable solvent-resistant membranes for angstrom-sized molecular separation - Zhang, Yanqiu; Sun, Hongguang; Sadam, Hussain; Liu, Yuyan; Shao, Lu (Chemical engineering journal (Lausanne, Switzerland : 1996), 2019)
By combining the supramolecular chemistry and membrane science, the biocompatible CD with the inherent cavity (6.0–6.5 Å) and mussel-inspired polydopamine (pDA) can synergistically construct ultra-stable solvent-resistant membranes for angstrom-sized molecular separations via one-step “green” process. [Display omitted] •Supramolecular chemistry was first utilized to construct novel OSN membrane.•A sub-75 nm-thick selective layer was prepared by a one-step “green” process.•The novel membrane has an extraordinary stability in organic solvents.•The OSN membranes exhibited high rejection against angstrom-sized contaminants. Organic solvent nanofiltration (OSN) membrane is an embryonic technology in chemical engineering for simultaneously purifying organic solvents and recycling nano-scale molecules. Although the inherent nano-cavity cyclodextrins (CDs) as powerful molecular hosts in supramolecular science ensure promise for separation technology, the limited synthesis toolbox and material choice impede the CDs deployment in membrane separations, especially for OSN applications. Herein, biocompatible β-cyclodextrin (β-CD) and mussel-inspired polydopamine (pDA) were discovered as the building blocks to simultaneously construct OSN membranes assisted by the host-guest interactions of supramolecular chemistry and hydrogen-bonds via one-step “green” process. Honeycomb microstructures were formed in this process, which adds the molecular transportation pathways. Such biopolymer membranes can remain extraordinarily stable in organic solvent environments, whilst achieving high rejection against angstrom-sized molecule with different charges toward environmental and energy benefits.